Japan's capitalism : - Tsuru, Shigeto (Cambridge University Press, 1996)
Contents: Japan's economic reconstruction after total defeat in the Second World War has been an extraordinary phenomenon. Shigeto Tsuru, one of Japan's most eminent economists gives a comprehensive account of the recovery process, and a unique interpretation of the postwar Japanese economy.